The Improvement of Scientific Attitudes through Problem-based Learning with Differentiated Instruction in Physics Subject - Windarto, Yusfrina Yanuarti; Pranata, Pranata; O, Okimustava (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to improve the scientific attitude of XG students at SMA N 1 Purworejo through the application of the Problem-Based Learning (PBL) model with a differentiation approach in physics education. This research is a classroom action research conducted over two cycles. Data were collected through observations using an observation sheet. The results from Cycle I showed an average class score of 71% out of 100%, with three out of nine indicators rated as